2015
DOI: 10.1016/j.jpsychores.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and coping in physical health conditions: A meta-analysis

Abstract: Illness perceptions and coping have an important role to play in the explanation of distress outcomes across a range of physical health conditions. However, some clarity about the theoretical position of coping in relation to illness perceptions, and further longitudinal work is needed if we are to apply this information to the design of interventions for the improvement of psychological health among people with physical health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 53 publications
10
161
1
6
Order By: Relevance
“…Our higher rates for 12-month mood disorders seem to be a more appropriate indication of the true morbidity rate than the 4-week diagnoses, because they describe the psychopathology and course of affective syndromes more appropriately and take into account that many subjects with threshold diagnoses in the past 12 months are likely to be only partially remitted. Further the 12-month time frame takes better into account the middle- and long-term consequences of the cancer and cancer treatments such as fatigue, pain, lower quality of life, illness perceptions and maladaptive coping strategies [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Our higher rates for 12-month mood disorders seem to be a more appropriate indication of the true morbidity rate than the 4-week diagnoses, because they describe the psychopathology and course of affective syndromes more appropriately and take into account that many subjects with threshold diagnoses in the past 12 months are likely to be only partially remitted. Further the 12-month time frame takes better into account the middle- and long-term consequences of the cancer and cancer treatments such as fatigue, pain, lower quality of life, illness perceptions and maladaptive coping strategies [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…It seems to be well established in the literature that avoidance strategies are good predictors of psychological distress (Dempster et al, 2015), and that direct action coping strategies focused on problem solving lead to emotional benefits and better adaptation to medical situations (Stanton et al, 2000;Stanton & Low, 2012). It has been found that in breast cancer, which represents the majority of cases in our sample, stress avoidance strategies are prejudicial depending on other variables, such as the stage of the illness or whether it is being treated (Asuzu & Elumelu, 2013;Costanzo, Lutgendorf, Rothrock, & Anderson, 2006;Kraemer et al, 2011;Kvillemo & Bränström, 2014;Moskowitz, Hult, Bussolari, & Acree, 2009).…”
Section: Discussionmentioning
confidence: 70%
“…The relationship of coping styles to wellbeing during the course of the illness as a source of stress has been widely studied, and how individuals confront the disease has been revealed as important to the health outcome and managing consequences (Livneh & Antonak, 2005;Dempster, Howell, & McCorry, 2015). Acceptance and positive reevaluation as styles of approaching the problem have been related to more well-being, and disengagement and avoidance to less.…”
mentioning
confidence: 99%
“…How patients perceive their illness can predict how they manage the illness and what their health outcome will be [14][15][16]. Other studies [10,17] have reported that how patients with schizophrenia perceive their illness affects their adherence to their medication regimen.…”
Section: Illness Perception Defined As What Patients Believementioning
confidence: 99%